ANALISIS YURIDIS TERHADAP PENERAPAN SANKSI BAGI OPTIK YANG TIDAK MEMPEKERJAKAN REFRAKSIONIS OPTISIEN TERSERTIFIKASI BERDASARKAN UNDANG-UNDANG KESEHATAN - Riono, YV Agung; Tuanaya, Halimah Humayrah; Simarmata, Murni (Akademi Refraksi Optisi dan Optometry Gapopin, 2025)
The mandate for optical facilities to employ certified Refraksionist Optisien (RO) or Optometrists is a critical component of Indonesia's health quality assurance system, as reinforced by Health Law Number 17 of 2023. Non-compliance poses significant risks to patient safety and the integrity of eye care services. This study aims to analyze the legal sanctions imposed on optical facilities that fail to employ certified ROs, utilizing the IRAC (Issue, Rule, Application, Conclusion) method for legal analysis. The analysis is based on a comprehensive review of primary legal sources: Law No. 17 of 2023, Government Regulation No. 28 of 2024, the Minister of Health Regulation No. 19 of 2013 on Optical Practice, and other relevant derivative regulations. The discussion reveals a structured, multi-tiered sanction system grounded in legal theories of compliance and regulatory enforcement. Administrative sanctions range from written warnings and temporary operational suspension to license revocation and substantial administrative fines. Criminal sanctions, including imprisonment and larger fines, are applicable, particularly if the violation results in harm to a patient's health. The study concludes that the legal framework is sufficiently robust from a theoretical perspective. However, its effectiveness hinges on consistent supervision by local health departments and digital integration of professional certification databases. Ensuring compliance is not merely a legal formality but a fundamental ethical obligation to protect public health and align with global standards for quality eye care.